Multi-dimensional analysis of the global burden of colorectal cancer disease from 1990 to 2021 and prediction of future trends: A comprehensive study based on the GBD database - Yilan Sun; Guangyi Zhu; Dongbo Lian; Buhe Amin; Guangzhong Xu; Jing Wang; Nengwei Zhang; Dezhong Wang (PLoS ONE, 2025)
Background Colorectal cancer (CRC) is one of the malignancies with high morbidity and mortality rates worldwide, and its disease burden continues to increase with population aging and changes in lifestyle and dietary habits. Based on the Global Burden of Disease database (GBD), this study analyzed trends in global CRC incidence, deaths, and disability-adjusted life years (DALYs) from 1990 to 2021, and explored health inequalities across countries and regions. Methods This study used data from the GBD Database 2021 to quantify the contribution of population aging, population growth, and epidemiological changes to the burden of CRC. Health inequalities were assessed on a global scale through the Slope index (SII) and concentration index (CI), and the potential room for improvement in the control of DALYs burden in CRC was assessed by countries using frontier analysis. The future disease burden of CRC was predicted based on a Bayesian Age-Period-cohort model (BAPC). Results Worldwide, the incidence, death and DALYs burden of CRC increased significantly, mainly driven by population aging and population growth. Areas with high socio-demographic index (SDI) have significantly reduced the burden of disease through epidemiological changes, while the burden remains higher in areas with low SDI. Health inequalities have improved, but areas with low SDI still face a higher burden of disease. Frontier analysis shows that there is still much room for improvement in CRC prevention and control in countries with high SDI. Projections show that despite the decline in CRC deaths, the number of cases of CRC is expected to continue to increase due to the impact of population aging and population growth. Conclusions Population aging and growth drive the global CRC burden increase. Low – SDI regions’ epidemiological changes have limited impact. Future policies should focus on low – SDI areas’ early prevention and screening and optimize resource allocation.